PENGARUH CURRENT RATIO (CR) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-2024 - Nuraliza Nabila Rahmah; Siti Rusidah; Nurul Wahyuni; Novia Nour Halisa (Business Administration, FISIP ULM, 2025)
Nuraliza Nabila Rahmah, 2110412220015, 2025. The Influence of CR and EPS on Stock Prices in Telecommunication Sub Sector Companies Listed on the IDX 2017-2024, under the guidance of: Siti Rusidah. This research aims to analyze the partial and simultaneous influence of the CR and EPS on stock prices in telecommunication sub sector companies listed on the IDX 2017-2024. A quantitative research desaign, the study utilized purposive sampling to select 32 samples. Secondary data were collected from financial reports, and analyzed through multiple linear regression. The result reveal that the CR does not have a significant partial effect on stock prices in telecommunication sub sector companies listed on the IDX during the period 2017-2024. EPS has a significant partial effect on stock prices in the same companies. Furthermore, CR and EPS simultaneously have a significant effect on stock prices in telecommunication sub sector companies listed on the IDX 2017-2024.